Нематеріальні активи: основи бухгалтерського обліку та оцінки - Артеменко, Наталія Вікторівна; Ширяєва, Наталя Володимирівна (НТУ "ХПІ", 2015)
Нематеріальні активи є важливим об’єктом бухгалтерського обліку за своїми характеристиками, своїм складом, за рівнем впливу на результати господарської діяльності та фінансовий стан підприємства. У данiй статтi розкрита сутнiсть поняття «нематеріальні активи», розглянуто нормативно-правову базу з питань обліку нематеріальних активів, виявлено проблеми, пов’язані з оцінкою, а також запропоновано шляхи їх вирішення. Недосконалість законодавчої бази та класифікації об’єктів нематеріальних активів, розширення сфери використання нематеріальних активів, недостатня розробка методики оцінки зумовлюють потребу в удосконаленні їх обліку.

Intangible assets are an important object of accounting for its characteristics, its composition, in terms of impact on the results and financial position. In this paper revealed essence of the concept of "intangible assets", considered legal framework for accounting intangible assets identified problems associated with the assessment and proposed solutions. Actual problems of modern accounting is the ability to reliably display information about intangible assets in the financial and other types of reporting. The key to this is the process of determining the actual scientific and reasonable value of intangible assets - evaluation. The peculiarity of the latter is the availability of targeted and no single universal method. Accurate and scientifically - grounded assessment is of particular importance in the inclusion of intellectual property to the charter capital, the merger of companies or organizations to determine the division of property units in the authorized capital in financial reporting, assessing collateral obtained loan losses determination in identifying abuse rights to intellectual property. Imperfect legal framework and classifications of intangible assets, expansion of the use of intangible assets is insufficient to develop methods of assessment determine the need to improve their records. The impact on the theory and practice of accounting in general and intangible assets, in particular, has its transformation to international standards. There is no doubt need to address these issues in existing international experience, but with reference to domestic realities, as well as close to the theoretical achievements of the current practice.
Intangible assets: basis of record-keeping and estimation
Keywords: активи підприємства; ефективність використання; право власності; первісна вартість; амортизація; authentication; efficiency of the use; primitive cost; depreciation; right of ownership